Particle Flow Analysis of Macroscopic and Mesoscopic Failure Process of Salt Rock under High Temperature and Triaxial Stress - Haoran Li; Ziheng Wang; Dekang Li; Yajun Zhang (Geofluids)
In order to reveal the mechanism of thermal-induced deformation and fracture development of salt rock under high temperature, the particle flow program PFC2D was used to study the triaxial compression failure process of salt rocks under different temperatures; at the same time, a combination model of Burge and Linearpbond was proposed to simulate plastic deformation and heat conduction of salt rock. Finally, the simulation results were compared with the experimental results to verify the validity of the conclusion. The simulation results show that the elastic limit points of rock gradually descend, the dilatancy points rise gradually, and the plastic deformation characteristics of salt rock become more obvious with the increase of temperature. Due to the damage of the sample, the strong chains break and disappear, increasing the proportion of the weak chains, and the high temperature intensifies the rupture of the contact between the particles in the salt rock. As the temperature increases from 50°C to 120°C, the strong chains in the rock sample decrease significantly, and the damage gradually increases; when the temperature is 150°C, the contact force decreases sharply, and the damage of salt rock is significant. According to the particle displacement cloud diagrams, it is found that the expansion direction from the middle part of the rock sample to the left and right ends is 12.08°, 9.55°, 8.2°, 6.33°, and 0°, respectively. The displacement directions of the rock sample show obvious radial expansion tendency, and the higher the temperature, the more obvious the “drum-shaped” failure phenomenon in the middle of the rock sample. During the heating process, the thermal cracks are mainly tensile cracks, and transverse cracks are gradually formed in the middle of the model. The cementation failure points at the top and bottom of the model expand in an oblique direction and form oblique cracks of about 45°. From the three different mathematical models of macroscopic and mesoscopic views, it is concluded that the effect of temperatures on salt rock is more significant after 90°C. This research is important for exploring the macroscopic and microscopic mechanics evolution of salt rock and provides a reference for determining the long-term mechanical strength of salt rock.